Scalable hot carrier–assisted silicon photodetector array based on ultrathin gold film - Kim Geunpil; Kim Hyebi; Jeon Young-Uk; Kim In Soo; Kim Soo Jin; Kim Sangsik; Kim Jongbum (Nanophotonics, 2024)
Silicon (Si) offers cost-effective production and convenient on-chip integration for photodetection due to its well-established CMOS technology. However, the indirect bandgap of Si inherently limits its detection efficiency in the near-infrared (NIR) regime. Here, we propose a strategy to achieve high NIR photoresponse in Si by introducing a strong light-absorbing ultrathin gold (Au) film to generate hot carriers. Using a 4.6 nm thick-Au film deposited on Si, we achieved photoresponsivity of 1.6 mA/W at 1310 nm under zero-bias conditions, and rapid temporal responses of 7.5 and 8 μs for rise and fall times, respectively, comparable to germanium (Ge) photodiodes. By utilizing an ultrathin (<6 nm) Au film as the light-detecting layer and thicker (>100 nm) Au film as electrodes, we introduce a unique approach to design a photodiode array based on a single metal (Au) platform. Comparative analysis with a commercial beam profiler image validates the performance of our designed array. This work presents an efficient strategy for manufacturing cost-effective and scalable NIR photodetector arrays, which eliminates the need for additional insulator layers.